The woman who inherited trouble [large type] - Crigger, C. K. (Crigger, C. K. Woman who, 2024)
"When January Billings receives a letter informing her not only of the death of a grandfather she knew nothing about, but also that a meeting with his attorney would be to her best advantage, she is both angry and intrigued. Eli Pasco convinces her to follow up on the matter. A second note warning her to stay away or else it might "prove bad for her health" only makes the decision easier. January is not a woman to be cowed by threats. Turns out her grandfather was enormously wealthy and he's left most of his fortune to January. Three male cousins expected to inherit the fortune and, one way or another, mean to see they do. Matters escalate when January meets two more unnamed heirs -- underage kids she begins to feel responsible for. Arson, arrows, kidnapping, and murder are all in the cousins bag of tricks. As January fights to stay alive and keep the kids safe, Eli and a few friends join her in her mission to see justice done."--